The Scholarship of Teaching and Learning Entrepreneurship. (January 2018) - Neck, Heidi M.; Corbett, Andrew C.
Entrepreneurship education (EE) research is not advancing as fast as general entrepreneurship because it is not subject to the same level of scholarship. Grounded in the Scholarship of Teaching and Learning from the field of adult education and using an expert Delphi Panel approach, we offer a glimpse into the minds of top entrepreneurship educators. We suggest studying EE through a teaching lens offers insights and elevates teaching as a form of scholarship on par with traditional, more accepted forms of research. Our Delphi analysis suggests a definition of EE as developing the mindset, skill set, and practice necessary for starting new ventures, yet acknowledging the outcomes of such education are far reaching. We introduce five continuums of EE that encourage a transition to teaching approaches based on adult learning, namely andragogy and heutagogy. Implications for entrepreneurship educator training, the need for practice, and the future of EE research are discussed.